(3bVGjG eYGUQIs - (3GSeGYjd jMji(B, (3GdJcQjJjs ((3YeGf(B:s (3OGQ GdMGeO(B,s, 2007)
(3GdeONd hGdeaghe ddeMGSHI GdGOGQjI ,eaGgje GdJcdaI hJUfjaGJgG ,JMdjd GdYdGbI Hjf GdJcdaI hGdMLe hGdQHM ,GdbQGQGJ GdGOGQjI bUjQI GdCLd ,GSJNOGe GdJcGdja aj bQGQJ GdJSYjQ ,GYOGO GdehGRfGJ GdQCSeGdjI ,GdehGRfGJ GdJNWjWjI ,GdQbGHI GdGOGQjI hJbGQjQ GdCOGA ,GdJYQja HeMGSHI GdJcGdja GdeYjGQjI ,JSLjd GdYedjGJ GdeGdjI aj Xd GSdhH GdcdaI GdeYjGQjIs
(3HHdjhZQGajG(B: (3U(B.421-422 ((3GbJfGAGJ (B2014 2(3f(B)s
Keywords: (3GdeMGSHI GdEOGQjIs; (3eMGSHI GdJcGdjas